TREATMENT OF BREAST CANCER WITH METASTATIC CONTRALATERAL AXILLARY LYMPH NODES: CASE REPORT AND LITERATURE REVIEW - V. A. Amosova; A. V. Petrovsky; M. V. Chernykh; E. I. Kovalenko; M. A. Frolova; R. K. Valiev; M. I. Nechushkin; V. U. Kirsanov; I. V. Vysotskaya; D. E. Avtomonov (Сибирский онкологический журнал, 2020)
Background. until now, only a few reports have been available on clinical management of breast cancer patients with metastases to the contralateral axillary lymph nodes. Breast cancer is traditionally considered to affect ipsilateral lymph nodes. However, there are many reports describing cases with contralateral axillary lymph node metastasis. Case presentation. We report a case of cancer in the right breast with contralateral axillary lymph node metastasis (Т2N1М1). Histological examination revealed invasive ductal G2 carcinoma with angiolymphatic invasion. No mutations in the BRca1, BRca2, cHEK2, and NBs1 genes were detected. the patient received complex treatment. Literature review. a PubMed search was conducted using the systematic review filter to identify articles describing cases with contralateral axillary lymph node metastasis. contralateral axillary lymph node metastasis, especially after surgery or radiotherapy, should be considered not only as hematogeneous metastasis but also as lymphagenous metastasis. survival of these patients is more comparable to that observed in patients with locally-advanced cancer than to that observed in patients with distant metastases. Conclusion. Early detection and management of contralateral axillary lymph node metastasis in breast cancer patients remains a debatable topic. Factors affecting disease prognosis have not been identified yet. Further studies concerning staging of contralateral axillary lymph node metastasis are needed.